Emulating Vehicular Ad hoc Networks for Evaluation and Testing of Automotive Embedded Systems - Schiller, Manuel; Knoll, Alois (EAI Endorsed Transactions on Smart Cities, 2015)
The evaluation and testing of cooperative applications based on Vehicular Ad hoc Networks (VANETs) in real testbeds is difficult due to the need for repeatable scenarios and large-scale experiments. Therefore a novel virtualization-based framework is presented to evaluate automotive software in the context of emulated VANETs. The approach enables the precise and large-scale evaluation of real-world implementations through the synchronized execution of network and vehicle simulators as well as the applications encapsulated in virtual Electronic Control Units. This paper provides a detailed description of the framework’s structure and its components as well as an validation of the proposed synchronization algorithm. The performance comparison with pure network simulation indicates that despite additional overhead large-scale experiments can be conducted without loss of accuracy.